2023
DOI: 10.3390/app13031496
|View full text |Cite
|
Sign up to set email alerts
|

Vumark’s Method of Production Layout Designing

Abstract: The paper deals with the issue of the mixed-reality usage in the design of production systems, its changes during expansion, or technological changes in the production, where it is necessary to flexibly and quickly verify the integration of a new machine into the existing layout and eliminate collision situations even before the installation of a physical machine in production. This is realized through Vumark’s design methodology, which was verified and applied in the conditions of the production environment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The selected approach makes it possible to quickly identify the ideal location for the machines in the layout solution by verifying multiple machine placement options during the trial. The experiment demonstrated that the selected approach is workable in real-world scenarios and results in time, money, and energy savings-particularly when modifying the production hall's architecture or machine [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The selected approach makes it possible to quickly identify the ideal location for the machines in the layout solution by verifying multiple machine placement options during the trial. The experiment demonstrated that the selected approach is workable in real-world scenarios and results in time, money, and energy savings-particularly when modifying the production hall's architecture or machine [7].…”
Section: Literature Reviewmentioning
confidence: 99%